A call for a paradigm shift: Assumed‐to‐be premature migrants actually yield good returns. Issue 1 (13th July 2018) - Birnie‐Gauvin, Kim; Aarestrup, Kim
Abstract: Animals with complex life cycles often display plasticity in the timing of transitions across life stages. The brown trout, Salmo trutta, highlights such phenotypic plasticity with its alternative migratory tactics. Downstream migration of smolts exemplifies one of the many ways in which brown trout display plasticity. The timing of this migration is assumed to be in the spring, although recent evidence suggests an autumn migration is also present. While the proximate and ultimate causes for this autumn migration remain unclear, it was hypothesised that leaving in the autumn may have short‐term benefits (e.g., lower competition) but that these individuals are maladapted to life at sea and yield poor adult returns. To test this hypothesis, 1370 wild juvenile brown trout from a Danish stream were tagged with PIT tags. Individuals were then divided into autumn and spring migrants depending on the timing of their outmigration to saltwater, and their return to freshwater was followed. Inconsistent with the hypothesis that autumn migrants yield poor returns, our findings suggest that autumn migrants yield similar return rates to spring migrants, with no observed differences in length, mass and condition upon tagging, nor in average time spent at sea. Our findings suggest that autumn migrants may not be maladapted to marine environments in a way that affects their survival, and call for a paradigm shift in the current description of the brown trout lifecycle.